FOSTERING 21st CENTURY SKILLS USING AN ONLINE DISCUSSION FORUM IN AN ENGLISH FOR SPECIFIC PURPOSE COURSE (Malaysian Journal of Learning and Instruction, 2021)
Purpose – This study explored English for Specific Purpose (ESP) students’ utilisation of an online discussion forum (ODF) via the university Learning Management System to assist them in executing their group project task of constructing a Company Profile.Methodology – A case study was employed, guided by Socio-Constructivism theory and the Partnership for 21st Century Learning framework. A total of 26 undergraduates participated voluntarily in the ODF. The group project was carried out virtually among group members in three online sessions. Prior to the project, students were briefed by the instructor, who posted questions to students via the portal in stages to carry out the discussion online. Besides the online postings, students wrote about the ODF experience in their reflective journals and took part in interviews. The data were qualitatively analysed.Findings – Students valued the learning experience and perceived the ODF as beneficial in facilitating English language learning as well as fostering 21st century skills. The positive impact on English language learning was realised in students’ linguistic attainment. Meanwhile, flexibility trait, reference for documentation, confidence increase and attentiveness provision were identified as factors that influenced the students’ optimistic views on the use of the ODF. The students also saw the online environment as an inclusive venue for developing critical thinking, leadership, discipline, time management and digital skills. Significance – The study demonstrated the potential of ODF as a convenient and flexible platform that is able to promote linguistic improvement among students through discussions and knowledge sharing relative to the assigned group task. The non-threatening learning and the conducive atmosphere of their group discussion experience also supported active participation, giving passive students more opportunities to express their opinions confidently.